Contextual Effect of Community Health Center on Low Birtweight in East Lombok, Nusa Tenggara Barat - Rahayu, Baiq Zulvita; Budihastuti, Uki Retno; Rahardjo, Setyo Sri (Journal of Maternal and Child Health, 2019)
Background: Low birth weight babies (LBW) become a global health problem. Studies into the contextual effect of community health center on LBW are lacking. This study aimed to determine the contextual effect of community health center on the determinants of low birth weight in East Lombok, Indonesia using multilevel analysis.Subjects and Method: This was an analytic observational study with a cross-sectional design. It was conducted in East Lombok, from September to November 2018. A total sample of 200 infants from 25 community health centers was selected by random sampling. The dependent variable was LBW. The independent variables were maternal age, maternal education, family income, prenatal stress, maternal nutritional status, exposure to cigarette smoke, maternal occupation, social support, and social capital. The data were collected from the medical record and questionnaire. The data were analyzed by a multilevel multiple logistic regression analysis.Results: Maternal age <20 or ≥35 years (b = 2.60; 95% CI = 0.96 to 4.25; p= 0.002), prenatal stress (b = 1.30; 95% CI 95%= 0.01 to 2.57; p= 0.048), and exposure to cigarette smoke (b= 1.57; CI 95% = 0.37 to 2.76; p= 0.010) increased the risk of LBW. LBW decreased with high maternal education (b = -1.38; 95% CI= -2.60 to -0.15; p= 0.027), high family income (b= -1.32 ; 95% CI = -2.61 to -0.04; p= 0.072), strong social support (b= -1.50; 95% CI= -2.92 to -0.09; p= 0.036), good maternal nutritional status (b = -2.01; 95% CI= -3.26 to -0.76; p= 0.002), strong social capital (b= -1.45; 95% CI= -2.82 to -0.08; p=0.038), and maternal occupation (b= -1.43; 95% CI= -2.98 to 0.12; p= 0.072). Community health center had contextual effect on LBW with ICC= 20%.Conclusions: Maternal age <20 or ≥35 years, prenatal stress, and exposure to cigarette smoke increase the risk of LBW. LBW decreases with high maternal education, high family income, strong social support, good maternal nutritional status, strong social capital, and maternal occupation. Community health center has contextual effect on LBW.Keywords: low birth weight, stress, social support, community health centerCorrespondence: Baiq Zulvita Rahayu. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami No. 36 A, Surakarta, Central Java 57126, Indonesia. Email: rahayubaiq.zulvita@yahoo.co.id. Mobile: +6281917744469Journal of Maternal and Child Health (2019), 4(3): 136-145https://doi.org/10.26911/thejmch.2019.04.03.01